Gender-Based differences in health attitudes among students as a psychological and pedagogical issue - G. Kodzhaspirov, Yury (2020)
Our attitude to health, its protection and maintenance, is not only a personal issue, but a social one as well. The university years are a time when young people are actively shaping their personal values and views of the world.  Examining how students view their health, and what efforts they make to preserve it, is of relevance not only for medical and social studies, but also for psychological and educational ones, as we need to understand what can be done during the university years to shape the right health behaviors, and how to do it. In psychological and educational studies, gender plays a crucial role in shaping the issues in question.